BASIC LINGUISTIC NOTIONS IN THE METHODOLOGY OF ORTHOGRAPHIC DRILL FOR 8-9 FORM STUDENTS (Proceedings of Southern Federal University. Philology, 2014)
The article is concerned with the problem of development of students' speech competences during the orthographic practice at the Russian language lessons at 8-9 forms of comprehensive secondary school. The author states that knowing the language rules helps to understand the language efficient functioning The author emphasizes that speech and linguistic felicities of school students can be successfully formed during the process of text creation, perceiving and understanding. The strategic objective of 8-9 form students' orthographic literacy improvement becomes the basis for the formation of their communicative skills. Keywords: language, speech, speech education, orthography, text, communicative skills.Author: Ostanina Yu.O.